Corticosteroids regulate brain hippocampal 5-HT1A receptor mRNA expression - Chalmers, DT (J Neurosci, 1993)
Using in situ hybridization techniques, the expression of 5-HT1A receptor mRNA was measured within the hippocampal formation after bilateral adrenalectomy (ADX). After 24 hr ADX, 5-HT1A receptor mRNA expression was significantly increased in all hippocampal subfields in ADX animals relative to sham-operated controls (SHAM). The magnitude of the increase was most pronounced within CA2 (127%) and CA3/4 (94%)- subfields of dorsal hippocampus, intermediate in the dentate gyrus (73%), and least within CA1 (60%). Administration of exogenous corticosterone (CORT) at the time of ADX maintained the level of 5-HT1A receptor mRNA expression within the range of SHAM animals. In vitro receptor autoradiographic analysis of 5-HT1A receptors in adjacent sections from the same animals indicated a simultaneous increase in 5- HT1A binding throughout the hippocampus in response to ADX. 5-HT1A binding increased to a similar extent (approximately 30%) in CA subfields and dentate gyrus but remained within SHAM levels in CORT- replaced animals. 5-HT1A receptor mRNA levels were also increased in hippocampal subregions of 1 week ADX animals relative to SHAM animals. Within both CA1 and CA2 subfields, the increments were approximately double those observed after 1 d ADX. 5-HT1A receptor binding was increased in every hippocampal subfield to a similar extent as that observed after 1 d ADX. Increases in both 5-HT1A receptor mRNA expression and 5-HT1A receptor binding were preventable by administration of exogenous CORT at the time of ADX. Hippocampal 5-HT1C receptor mRNA and D1 receptor mRNA expression were not significantly altered by either acute or chronic ADX treatment. These data indicate that adrenal steroids may selectively regulate hippocampal 5-HT1A receptors at the level of 5-HT1A receptor mRNA expression.